A new subtype of a congenital disorder of glycosylation (CDG) with mild clinical manifestations - Assmann, Birgit; Hackler, R.; Peters, Verena; Schaefer, J. R.; Arndt, T.; Mayatepek, Ertan; Jaeken, J.; Hoffmann, Georg F. (Neuropediatrics, 2001)
Thieme E-Books & E-Journals